Cannon score (dedicated to Cannonball Aderley), for flute, humming on flute and pre-recorded sounds (Per Musi, 2010)
Cannon was recorded and transcribed by Hermeto Pascoal in the album Slaves Mass (1977). This complete edition was reviewed and edited by Fausto Borém (2010), from the recording and the spiral score designed by Ruy Pereira on the inside cover of the disc.